TINDAK TUTUR DIREKTIF DALAM NOVEL CALABAI KARYA PEPI AL-BAYQUNIE - isnaeni isnaeni; Lukman Lukman; Noer Jihad Saleh (JURNAL ILMU BUDAYA, 2022)
This study aims to map the form of directive speech acts used in Pepi Al-Bayqunie's novel Calabai. The type of research is descriptive qualitative that uses two approaches, namely a theoretical approach and a methodological approach. The research data is in the form of fragments of speech in a novel that contains symptoms of speech acts. The data comes from a novel entitled Calabai by Pepi Al-Bayqunie. This novel with a thickness of 383 pages was written based on the true story of bissu in Pangkep Regency, South Sulawesi Province. The results showed that there were 10 forms of directive speech acts in Pepi Al-Bayqunie's novel Calabai, namely ordering, advising, ordering, pleading, recommending, reprimanding, forbidding, inviting, asking, and criticizing. Among all these forms, the form of advising is the most common. This means that calabai is synonymous with advising others.